Cotinine Overcome the Decrease of Prostacyclin Formation Induced by Nicotine after Sympathetic Stimulation in Microsomes from Isolated Rabbit Heart - G. Ammar, R. Nemr, Z. Dagher, S Khairallah, R. Chahine (Journal of Applied Pharmaceutical Science, 2013)
We studied the effects of cotinine, the major metabolite of nicotine, on nicotine-induced decrease in prostacyclin (PGI2) synthase activity of microsomes from isolated rabbit heart after sympathetic stimulation. Rabbit hearts were isolated along with their sympathetic nerves and perfused in accordance to the Langendorff method. Hearts were randomly divided into 10 groups treated with cotinine, either during sympathetic stimulation or prior to nicotine administration. PGI2 formation in cardiac microsomes was assessed by radioimmunoassay. The results showed that sympathetic stimulation increased PGI2 synthase activity of heart microsomes by 32 %. Nicotine dose dependently decreased PGI2 while cotinine increased it. In addition, perfused before nicotine, cotinine prevented the PGI2 decreasing effect of nicotine. The results suggest that pre-treatment with cotinine can be involved in the modulation of nicotine effects on PGI2 in hearts subjected to sympathetic stimulation.
Keywords: Isolated heart, Sympathetic stimulation, Nicotine, C